Exploring the gendered dimensions of meaningful non-profit work under marketised conditions. (1st March 2022) - Sandberg, Billie; Robichau, Robbie Waters; Russo, Andrew
Abstract : Neoliberal marketisation is altering the nature of non-profit work, leaving workers to navigate a 'double bind' of mission- and market-based values. Some feminist scholars suggest these dynamics are particularly challenging for female workers. Drawing on a larger study of meaningful non-profit work and neoliberal marketisation as well as on contemporary critical and feminist scholarship, this exploratory study examines how neoliberalism's entrepreneurial subject manifests along gender lines among non-profit managers. Data from interviews with 28 non-profit managers demonstrate that while both men and women evoke elements of neoliberalism's entrepreneurial subject, female managers wrestle more with conflicting discourses of market and mission values and rhetoric as well as sociocultural expectations around gender, resulting in a 'triple bind'. This article suggests that neoliberal market discourses are impactful in the manner suggested by feminist scholarship but not necessarily totalising nor deterministic.